Targeted Bleeding Management Reduces the Requirements for Blood Component Therapy in Lung Transplant Recipients. Issue 4 (August 2017) - Smith, I.; Pearse, B. L.; Faulke, D. J.; Naidoo, R.; Nicotra, L.; Hopkins, P.; Ryan, E. G.
Abstract : (Abstracted from J Cardiothorac Vasc Anesth, 31:426–433, 2017) High rates of bleeding and allogeneic blood transfusions to treat bleeding are associated with adverse outcomes in bilateral sequential lung-transplant patients. The aim of this study was to determine if point-of-care coagulation testing could minimize unnecessary transfusion in lung-transplant patients.